2011
DOI: 10.1016/j.jpowsour.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the discharge reservoir of negative electrodes in Ni–MH batteries by using Ni(OH) (x= 2.10) and γ-CoOOH

Abstract: a b s t r a c tIn this paper, a novel strategy to regulate the discharge reservoir of negative electrodes in Ni-MH batteries is introduced by using Ni(OH) x (x = 2.10) and ␥-CoOOH. The electrochemical measurements of these batteries demonstrate that the use of Ni(OH) x (x = 2.10) and ␥-CoOOH can not only successfully regulate the discharge reservoir of negative electrodes in Ni-MH batteries to an adequate quantity, but also effectively improve the electrochemical performance of the batteries. Compared with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Oxides, hydroxides and oxyhydroxides of nickel are of interest as electrode materials for rechargeable batteries [1][2][3][4][5][6][7][8]. Nickel (II) hydroxide occurs in at least three polymorphs, α, β and γ, and transitions with nickel (III) oxyhydroxide in a redox reaction at battery electrodes during charging and discharging.…”
Section: Introductionmentioning
confidence: 99%
“…Oxides, hydroxides and oxyhydroxides of nickel are of interest as electrode materials for rechargeable batteries [1][2][3][4][5][6][7][8]. Nickel (II) hydroxide occurs in at least three polymorphs, α, β and γ, and transitions with nickel (III) oxyhydroxide in a redox reaction at battery electrodes during charging and discharging.…”
Section: Introductionmentioning
confidence: 99%
“…the D 50 value of samples A, B, C, D and E are 25.38, 23.54,26.08, 24.47 and 23.92 mm, respectively, indicating that the effect of the anions on the particle size of a-Ni(OH) 2 is slight under the same preparation conditions. The tap-densities of samples A, B, C, D and E are 1.89, 1.63, 1.92, 1.56 and 1.88 g cm À3 , respectively, demonstrating that to some extent the interlayer anions affect the tapdensity of the end product.…”
mentioning
confidence: 88%
“…Consequently, it is imperative to enhance the tap-density of Al-substituted a-Ni(OH) 2 for its practical use. In the previous work [25,26], we have studied the effect of tap-density on the electrochemical performance of non-spherical b-Ni(OH) 2 electrodes and found that better electrochemical activity can be achieved for non-spherical b-Ni(OH) 2 with a higher tapdensity. The high-density b-Ni(OH) 2 materials exhibit a dense solid microstructure, which contains many overlapped sheet nano crystalline grains, and have a high density of structural disorder and a large specific surface area, resulting in an enhanced electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Nickel hydroxide is used as the positive electrode material but features poor electrical conductivity after its reaction to form NiOOH in the charging process. Hence, conductive materials, [10][11][12][13][14] or Co compounds [15][16][17][18][19][20][21] are usually added to the positive electrodes and methods for introducing these additives and their influence on battery performance have been extensively studied. [22][23][24][25][26][27][28][29] There have been many reports on the degradation mechanism of nickel metal hydride batteries.…”
Section: Introductionmentioning
confidence: 99%